Perlindungan Hukum Perempuan dari Pelecehan di Komentar TikTok - Nuri Asmi Rawi; Mutiara Nabila Putri; Sela Karunia Yuliani (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The development of digital technology, especially the TikTok platform, has created a new space for online gender-based violence (GBV) against women. Harassment in the comments section has become a phenomenon that dehumanises women. This research aims to (1) describe the position of women as legal subjects in cases of harassment on TikTok according to the TPKS Law and the ITE Law, and (2) analyse the factors that cause the effectiveness of legal protection to be not optimal. This research uses a normative juridical method with a statutory and conceptual approach. The results of the analysis show that normatively, women are protected by the Constitution and specifically by the TPKS Law which categorises this harassment as electronic-based sexual violence, as well as the ITE Law. However, its effectiveness is hampered by procedural and structural obstacles, such as the difficulty of digital proof, anonymous perpetrators, and the low gender sensitivity of law enforcement officials. Existing protections are still formalistic. Therefore, normative reconstruction is needed through strengthening technical regulations, applying the principle of duty of care for platforms, and institutional synergy.